T Cell Immunity Evaluation and Immunodominant Epitope T Cell Receptor Identification of Severe Acute Respiratory Syndrome Coronavirus 2 Spike Glycoprotein in COVID-19 Convalescent Patients - Li, Luo; Chen, Qian; Han, Xiaojian; Shen, Meiying; Hu, Chao; Chen, Siyin; Zhang, Jing; Wang, Yingming; Li, Tingting; Huang, Jingjing; Li, Shenglong; Hao, Yanan; et al. (Frontiers in Cell and Developmental Biology, 2021)
A better understanding of the role of T cells in the immune response to SARS-CoV-2 is helpful not only for vaccine development, but also for the treatment of COVID-19 patients. We used a matrix of overlapping peptides spanning the entire SARS-CoV-2 spike glycoprotein to study T cell responses from 8 COVID-19 convalescent patients. Although all participants exhibited SARS-CoV-2 T cell responses to multiple regions of S protein, the specific T cell response in the RBD region was the weakest. We identified 11 peptides containing CD4+ and /or CD8+ epitopes, and the frequency and epitopes of SARS-CoV-2-specific CD4+ T cells were higher. We isolated the SARS-CoV-2-specific CD4+ T cell receptors (TCRs) and inserted the TCRs into allogenic CD4+ T cells. These TCR-T cells can be activated by SARS-CoV-2 S peptide and produce IFN-γ in vitro. These results might provide valuable information for the development of vaccine and new therapies against COVID-19.